1984
DOI: 10.3382/ps.0631722
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Toe-Clipping and Stocking Density on Laying Hen Performance

Abstract: Three experiments were conducted to investigate the influence of toe-clipping and bird density on laying hen performance. Toe-clipping was done on day-old chicks by removal of the digital claws from the front toes. Toe-clipped (TC) and intact (IN) pullets were assigned randomly to laying cages (Experiments 1 and 2, 19 weeks of age) or housed in similar body weight groups (Experiment 3, 18 weeks of age) at caging densities of either 4 (465 cm2/hen) or 5 (372 cm2/hen) hens per cage. Experiment 3 body weight grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
2

Year Published

1986
1986
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 12 publications
2
3
0
2
Order By: Relevance
“…Findings of Hill and Hunt (1978), Cunningham andOstrander (1981, 1982), Cunningham (1982), Ouart and Adams (1982), Roush et al (1984), and Goodling et al (1984) generally support these conclusions. Adams and Craig (1985), in a survey of research on effects of crowding on cage layer performance, suggested that a curvilinear relationship exists, with performance traits decreasing more rapidly at higher den-Scientific article Number 1950, West Virginia University Agricultural Experiment Station.…”
Section: Introductionsupporting
confidence: 82%
“…Findings of Hill and Hunt (1978), Cunningham andOstrander (1981, 1982), Cunningham (1982), Ouart and Adams (1982), Roush et al (1984), and Goodling et al (1984) generally support these conclusions. Adams and Craig (1985), in a survey of research on effects of crowding on cage layer performance, suggested that a curvilinear relationship exists, with performance traits decreasing more rapidly at higher den-Scientific article Number 1950, West Virginia University Agricultural Experiment Station.…”
Section: Introductionsupporting
confidence: 82%
“…Garcia et al (1993), Adams & Craig (1985), Davami et al (1987) and Okpokho et al (1987) also found that increasing cage density and reduction of feeder space/bird caused a decline in egg production. Egg weight results obtained in the present study were similar to those obtained by Al Rawi et al (1976), Goodling (1984), Mench et al (1986), Lee (1989), and Carey et al (1995), who also did not find any effect of cage density on egg weight, whereas Roush et al (1984), observed a trend of increasing egg weight as cage area per bird was reduced. Davami et al (1987) found that egg weight decreased in the treatment of highest density.…”
Section: Methodssupporting
confidence: 90%
“…Por outro lado, Al Rawi et al (1976), Goodling (1984), Mench et al (1986), Lee (1989) e Carey et al (1995 não encontraram efeito da densidade na gaiola sobre o peso dos ovos. Davami et al (1987) constataram que o peso dos ovos diminuiu no tratamento de maior densidade.…”
Section: Resultsunclassified